Ice Skating - Belloni, E.; Sabbioni, E.; Melzi, S. (The engineering approach to winter sports, 2016)
The text proposes a overview about ice skating. It is not considering the figurative ice skating, but only the ice speed-skating. Furthermore, only few hints will be provided about the olltdoor skating, focusing then on the indoor competitions. After an historical reconstruction of the origins of this sport, the analysis will be divided into two main blocks: the dynamical model and the aerodynamic analysis of a speed skater (both numerical and experimental). Few notes about the track will be discussed along the chapter.